A Case Study of Mental Accounting in The Sandwich Generation - Saputri, Fidea Shela Chandra; Mustofa, Rochman Hadi (Universitas Muhammadiyah Surakarta, 2025)
This research aims to understand how mental accounting is in the sandwich generation. The sandwich generation is individuals squeezed between two generations with an age range of 50-60 years, with aging parents, children and even grandchildren. This research applies qualitative methods with a phenomenological approach through interviews. The sandwich generation emerged due to a lack of preparation and planning for the future. Mental accounting has a big influence on individuals in managing finances to make the right decisions. In the conditions of the sandwich generation, individuals are faced with the challenge of wise financial management to prevent financial problems at a young age. The application of mental accounting becomes relevant in making financial decisions. This shows that the sandwich generation applies the mental accounting process.